Elevated Plasma Ceramides Are Associated With Antiretroviral Therapy Use and Progression of Carotid Artery Atherosclerosis in HIV Infection. Issue 17 (23rd April 2019) - Zhao, Wei; Wang, Xueyin; Deik, Amy A.; Hanna, David B.; Wang, Tao; Haberlen, Sabina A.; Shah, Sanjiv J.; Lazar, Jason M.; Hodis, Howard N.; Landay, Alan L.; Yu, Bing; Gustafson, Deborah; et al.
Abstract : Background: Ceramides have been implicated in the pathophysiology of HIV infection and cardiovascular disease. However, no study, to our knowledge, has evaluated circulating ceramide levels in association with subclinical cardiovascular disease risk among HIV-infected individuals. Methods: Plasma levels of 4 ceramide species (C16:0, C22:0, C24:0, and C24:1) were measured among 398 women (73% HIV+) and 339 men (68% HIV+) without carotid artery plaques at baseline from the Women's Interagency HIV Study and the Multicenter AIDS Cohort Study. We examined associations between baseline plasma ceramides and risk of carotid artery plaque formation, assessed by repeated B-mode carotid artery ultrasound imaging over a median 7-year follow-up. Results: Plasma levels of C16:0, C22:0, and C24:1 ceramides were significantly higher in HIV-infected individuals compared with those without HIV infection (all P <0.001), and further analysis indicated that elevated ceramide levels were associated with antiretroviral therapy use, particularly protease inhibitor use, in HIV-infected individuals (all P <0.001). All 4 ceramides were highly correlated with each other ( r =0.70–0.94; all P <0.001) and significantly correlated with total-cholesterol ( r =0.42–0.58; all P <0.001) and low-density lipoprotein cholesterol ( r =0.24–0.42; all P <0.001) levels. Of note, C16:0 and C24:1 ceramides, rather than C22:0 and C24:0 ceramides, were more closely correlated with specific monocyte activation and inflammation markers (eg, r =0.30 between C16:0 ceramide and soluble CD14; P <0.001) and surface markers of CD4 + T-cell activation. A total of 112 participants developed carotid artery plaques over 7 years, and higher levels of C16:0 and C24:1 ceramides were significantly associated with increased risk of carotid artery plaques (relative risk [95% CI]=1.55 [1.29, 1.86] and 1.51 [1.26, 1.82] per standard deviation increment, respectively; both P <0.001), after adjusting for demographic and behavioral factors. After further adjustment for cardiovascular disease risk factors and immune activation markers, these associations were attenuated but remained significant. The results were consistent between men and women and between HIV-infected and HIV-uninfected participants. Conclusions: In 2 HIV cohorts, elevated plasma levels of C16:0 and C24:1 ceramides, correlating with immune activation and inflammation, were associated with antiretroviral therapy use and progression of carotid artery atherosclerosis. Abstract : Supplemental Digital Content is available in the text.